Microcrustacean diversity in the Gemenc-Béda-Karapancsa Floodplains (Danube-Drava National Park, Hungary): rare and alien species - Ágoston-Szabó, E. (Opuscula Zoologica Instituti Zoosystematici et Oecologici Universitatis Budapestinensis, 2015)
The composition of microcrustacean fauna was investigated in different water bodies of Gemenc-Béda-Karapancsa Floodplains with special regard to the distribution of alien and rare taxa. Between 2002 and 2013 101 taxa (57 Cladocera, 27 Copepoda, 17 Ostracoda,) were recorded from the water bodies with differing degrees of connectivity to the main river (eu-, para-, plesio- and paleopotamon). 18 species are reported for the first time from the area of Danube-Drava National Park and among them Daphnia ambigua, Pleuroxus denticulatus and Eurytemora velox are allochtonous species in Hungary. E. velox and P. denticulatus have persistent populations in the area, but their contribution to floodplain biodiversity is still not significant. Daphnia ambigua has only local and temporal populations and its presence is confined to the disconnected side of the floodplain. The abundance of thirty species was very low and their distribution pattern in the floodplain is different. The microcrustacean diversity of the plesiopotamal side arms is remarkable, particularly in the Nyéki-Holt-Danube.